THE EFFECT OF TRUST AND SERVICE QUALITY ON CUSTOMER SATISFACTION (A Study at Amarta-Elsa Nasution Swimming School, Malang) - Astri Kusuma Hidayati; Rini Rahayu Kurniati; Dadang Krisdianto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The competitiveness of service industries such as education and recreation has made customer satisfaction a crucial factor for business success. In this sector, swimming schools are not only required to give good instructions but also make sure that their customers are contented. Amarta-Elsa Nasution Swimming School found in Malang is an excellent case study to examine how trust, service quality and customer satisfaction interact with each other in a specific education context. Therefore, this research intends to find out the effect of trust and quality of service on customer satisfaction at Amarta-Elsa Nasution Swimming School located in Malang. A quantitative approach was utilized in this study, taking the saturated sample method, which is uses all the population of 65 respondents from all Amarta-Elsa Nasution Swimming School Malang student guardians. Questionnaires, observations, interviews and documentation were used to collect data in this study. In light of the study's findings, customer satisfaction at Amarta-Elsa Nasution Swimming School Malang is significantly influenced by trust. Furthermore, there exists a noteworthy connection among characteristics related to level of service and consumer happiness at Amarta-Elsa Nasution Swimming School Malang. Together, customer satisfaction at Amarta-Elsa Nasution Swimming School Malang is influenced by components related to trust and level of service.